(untitled) (University of Khartoum Journal of Agricultural Sciences, 2025)
Three irrigation frequencies and four tillage systems werestudied for two consecutive summer seasons (2002/03 and 2003/04) totest their effect on growth and yield of groundnut (Arachis hypogaea L.).The study was carried out in the Demonstration Farm of the Faculty ofAgriculture and Natural Resources, University of Kassala at New Halfa,Sudan. The irrigation frequencies were 10, 15 and 20 days, and the tillagesystems used were discing, ridging, harrowing and no-tillage. There weresignificant differences in the studied parameters due to irrigationfrequency. Except for days to 50% flowering and shelling percentage, the10 days frequency recorded higher values than 15 and 20 daysfrequencies. On the other hand, tillage system had significant effects onall tested parameters except 100-seed weight and shelling percentage.Disc ploughing gave higher values than the other tillage systems. Theinteraction between irrigation frequencies and tillage systems hadsignificant effects on the studied parameters except days to 50%flowering, seed weight and shelling percentage. Ten days irrigationfrequency with disc ploughing gave the highest yield and field water useefficiency.